Hubungan antara Komunikasi Keluarga dengan Kemampuan Bicara Anak Usia Dini Desa Rambai - Yani Andika; Vevi Sunarti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is motivated by the low ability to speak of early childhood in Desa Rambai Kecamatan Pariaman Selatan Kota Pariaman. This is allegedly due to poor communication in the family. This study aims to: (1) see communication in the family, (2) see the ability to speak of early childhood, (3) see the relationship between communication in the family and children's speaking ability in Rambai Village, South Pariaman District, Pariaman City. This type of research is quantitative correlational. The study population was 27 parents. Samples were taken as much as 70%, namely 20 people. Sampling technique with area random sampling. The data collection technique uses a questionnaire, while the data collection tool uses a questionnaire. Quantitative data analysis techniques use percentages while correlation analysis uses rank order and t test. The results showed that: (1) communication in the family had not been carried out properly, (2) speaking ability of early childhood in Rambai Village, South Pariaman District, Pariaman City in the low category, (3) there was a significant relationship between communication in the family and speaking ability of early childhood in Desa Rambai Kecamatan Pariaman Selatan Kota Pariaman.